CAS CIS CUS METODE MENDONGENG PADA ANAK USIA DINI - Nuryanto, Sidik (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Storytelling is an activity that is often found in the process of early childhood learning. Fairy tales are used by educatorsor teachers in order to entertain and instill character values. In the use of fairy tales in learning sometimes there are someproblems for both teacher and students. Teachers often find it difficult to start a story and close the story. At the time of theimplementation of the core of storytelling, the stories told have not been attracted the children’s attention to listen. Anotherproblem comes from the students that are difficult to be set to listen to the stories. The habit of guessing the storyline is also aproblem for teachers, so the storytelling is considered failed. Therefore, it takes a storytelling method which is helpful for teachersto implement and to attract the children’s attention. CAS CIS CUS is a story-telling method which divides story-telling intothree phases. CAS (Cipta Aksi Super – Super Action Creation) as a mean to open the story by attractive action to drawchildren’s attention. CIS (Cipta Inspirasi Super – Super Inspiration Creation) as the core of story-telling which containsinspiration or character values. CUS (Cipta Usulan Super – Super Idea Creation) as the closing f story-telling which containideas of character values followed by children.